Application of Arbuscular Mycorrhiza from Senaru Forest Rhizosphere for Gyrinops versteegii Germination and Growth - I Gde Adi Suryawan Wangiyana; Sukardi Malik (Biosaintifika: Journal of Biology & Biology Education, 2018)
The aims of this research are to apply Senaru forest  rhizosphere on Kabupaten Lombok Barat West Nusa Tenggara as Mycorrhiza inoculants for Gyrinops versteegii germination and growth. Rhizosphere sample was taken from ten sampling spot on Senaru forest between Latitude: 08o18.808’ S – 08o19.174’ S and Longitude: 116o24.138’ E – 116o24.181’E. This study employed Factorial Experiment Design with 2 Factor including: Medium Composition (M) and Mychorizza Inoculant (I). There were 5 media composition: M1 (sand), M2 (soil:sand = 1:2), M3 (soil:sand = 1:1), M4 (soil:sand = 2:1), M5 (soil). There were 2 types of Inoculation: I1 (without inoculant) and I2 (innoculant from senaru Rhizosphere). Growth parameters observed in this study were: germination percentage, stem length, stem diameter and root colonization. Germination percentage of G. versteegii seeds in all growth media are below 60 % which could be classified as low germination rate. Also germination from media without rhizosphere is higher than germination from media with rhizosphere. On the other hand, G. versteegii growth on rhizosphere media is slightly higher than growth of G. versteegii on media without rhizosphere based on stem diameter and length measurement. It tends that medium composition with higher sand proportion tended to gives better germination and growth rate of G. verteegii. Myorrhiza colonization on G. versteegii root was higher in media with rhizosphere addition. It could be concluded that Application of Senaru rhizosphere containing Mycorrhiza increases G. versteegii growth but not its germination percentage. This research enrich knowledge in biological science about asociation of mycorrhiza with G. versteegii especially on its growth and germination